Interiors of the semi-open pratoli of the Mahanaleshwar Temple Complex - Temples of India Project Team (Jio Institute, 2024)
This is a view of the interiors of the semi-open pratoli of the Mahanaleshwar temple complex. The central passage is flanked on both sides by verandahs with ruchaka pillars with square shafts. The pillar bases are carved with divine figures.